The Ruling Class of the Despotate of Epirus: A Research Attempt. Review of Denisov, S. A. (2017). Politicheskaia elita Epirskogo tsarstva v 1205–1261 gg. [Political Elite in the Principality of Epirus between 1205 and 1261]. Medievalia. Moscow; St Petersburg: Center for Humanitarian Initiatives. 398 p - Kushch, T. V. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2017)
This review analyses the new research of the ‘Epirus model’ of Byzantine statehood, the structure and political behaviour of the local ruling class. The reviewer emphases the topicality of the issue in question, concerning the history of the Despotate of Epirus, as well as the substantial source basis. She also underlines the importance of the prosopographic analysis conducted which helped reveal the structure of the ruling class of Epirus. The book under review focuses on the factors of consolidation between the clergy and members of local and newly come aristocracy close to the Doukai-Komnenoi dynasty, reasons for the stabilisation of the internal political situation in Epirus, and the principles of legitimation of the governor’s power. Special attention is paid to the author’s idea about the rallying of political elite at the initial stage of the Epirus state formation and its subsequent deconsolidation. The reviewer singles out some debatable issues connected with the study of the political history of the Despotate of Epirus.